Invasion factors of apicomplexan parasites: essential or redundant? - Meissner, Markus; Ferguson, David J. P.; Frischknecht, Friedrich (Current opinion in microbiology, 2013)
Apicomplexa are obligate intracellular parasites that cause several human and veterinary diseases worldwide. In contrast to most intracellular pathogens these protozoans are believed to invade a rather passive host cell in a process, that is, tightly linked to the ability of the parasites to move by gliding motility. Indeed specific inhibitors against components of the gliding machinery and the analysis of knockdown mutants demonstrate a linkage of gliding motility and invasion. Intriguingly, new data show that it is possible to block gliding motility, while host cell invasion still occurs. This suggests that either the current models established for host cell invasion need to be critically revised or that alternative, motor independent mechanisms are in place including a more active role of the host cell that can complement a missing actin-myosin-system. Here we discuss some of the discrepancies that need to be addressed for a better understanding of invasion.